KEKUATAN TUMBUH KECAMBAH AREN SETELAH PENYIMPANAN - Wahyuni, Dewi (Universitas Tadulako, 2017)
Aren (Arenga pinnata (Wurmb.) Merr have an important role in Indonesia, especially to support life of rural communities. Currently, aren plants are more directed to be a solution to overcome povertyÂ problems, environmental conservation, biofuel, food security, and employment of farmers. This study aims to study the technology of the acquisition of vigor aren sprouts, so that the vigor sprouts are ready to be bred in large quantities in a relatively short time to support the cultivation of palm trees. Through vigor testing the strength grows against drought on early growth of sprouts of aren seedlings. This research wasÂ conducting for five months, starting from December 2015 until April 2016, at Seed Technology Laboratory, Faculty of Agricultural, Tadulako University. This experiment used a Randomized Block Design with a separate plot factorial pattern. Each treatments was repeated three times. The treatment in this study consisted of two the main plots; first was normal sprouts that had passed the storage period (K)consisted of three levels, second was the plot of water availability condition(A), consisted of two levels. The results showed that the longer storage periode was produced the better viability and vigor of aren sprouts. The availability of field water capacity can increased the strength of sprout growth and it has significant effect on the growth component of sprouts of aren indicated by the length of plumula, total root length, and dry weight of sprouts. The 14-days storage period under field water capacity availability conditions demonstrated better sprout growth with plumula length and root length ratio, germination rate and improved germination rate.